Tafsir Sufistik Imam Khomeini: Pendekatan Irfani dalam Memahami Al-Qur’an - Siswoyo Aris Munandar (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2025)
Understanding the Qur'an in Islam has various methods of interpretation, one of which is the ‘irfānī or mystical interpretation, which emphasizes spiritual experience and the revelation of the inner meaning of the holy verses. One of the important figures who used this approach was Imam Khomeini, a thinker and spiritual leader who developed the interpretation of the Qur'an based on philosophical Sufism and direct experience of the essence of divinity. This study uses a library research method, by examining various primary and secondary sources that discuss Imam Khomeini's interpretation, both from his own writings and from the interpretations of Islamic scholars. This study aims to analyze the characteristics of Imam Khomeini's interpretation, trace his epistemological sources, and understand how the ‘irfānī approach in interpretation can contribute to the understanding of the Qur'an in the modern era. The results of this study Imam Khomeini's interpretation is one form of interpretation of the Qur'an that emphasizes the ‘irfānī (mystical) approach or isyari interpretation. Unlike conventional interpretation methods that prioritize textual and rational approaches, Imam Khomeini interpreted the verses of the Qur'an based on spiritual experience and esoteric dimensions. His interpretation of the concepts of rahman and rahim in Al-Fatihah, as well as his understanding of the manifestation of God in the universe, show the spiritual depth of his interpretation. This study aims to explore more deeply the characteristics of Imam Khomeini's interpretation and its relevance in the study of Islamic interpretation.